EXAMINING PRIMARY SCHOOL STUDENTS’ LEVELS OF MATHEMATICS MOTIVATION - Cumali Oksuz (European Scientific Journal, ESJ, 2015)
The aim of this study was to evaluate the levels of mathematics motivation of primary school students and to identify its relationship with variables such as sex, grade level, school type, general success and mathematics success. The number of participants in this study was 709 primary school students from Aydin city center. The sampling was comprised of 345 third grade and 364 fourth grade students. Data were collected through a scale titled as “Primary School Mathematics Motivation Scale” (PSMMS) developed by Ersoy and Oksuz in 2015. Findings gathered from the study illustrated that primary school students have a very positive motivation towards learning mathematics. Moreover, there was no significant difference, in students' math scores of motivation with respect to gender and their grade levels. However, depending on the type of school, there was a significant difference in students' math scores of motivation in favor of private schools. In addition to this, the level of students’ motivation in mathematics varied according to their level of overall academic success. The results also indicated that the level of students’ motivation in mathematics varied according to their level of mathematical academic success.